Standarisasi Jumlah Manpower Cleaning Services Perluas Area Pada Gedung United Tractors Head Office - Ulwan, Dzaki; Sekarlati Bernard, Fransiska; Fauziah, Usi (Teknoin, 2024)
In the era of intense global competition, companies must have the right strategy to achieve competitive advantage, one of which is by developing and managing human resources (HR) effectively and efficiently. In the United Tractors Head Office Building, distribution of cleaning services from PT. This disproportionate Mitra Bakti UT shows that the workload is not distributed evenly. Therefore, this research aims to measure the cleaning service workload in the United Tractors Head Office Building and determine the optimal number of workers needed using the Full Time Equivalent (FTE) method. and Work Load Analysis (WLA). In this research, the data taken is in the form of activities and the total hours of completion of these activities. By calculating the workload, you can see the correct number of celaning services and can determine the area of ​​each worker with an even workload. By using the Work Load Analysis method, the results are that the workload for cleaning services work is 250% compared to the existing workload of only 192%. The manpower workload is more balanced, previously the highest value was 104% and the lowest value was 43%, after calculating the workload it became evenly distributed with a value of 83%. After calculating the number of cleaning services from 20 people to 24 people and the area of ​​each manpower is 609 m^2.